Biopolymer nanoparticle production for controlled release of biopharmaceuticals. (June 2014) - Hudson, David; Margaritis, Argyrios
Abstract For drug applications, nanoparticles, used as drug carriers, offer the advantage of controlled release, therapeutic impact and targeted delivery. In drug delivery applications, biodegradable polymers can be extracted from natural sources or prepared synthetically by polymerization. Natural polymers typically have varying compositions and physiochemical properties. As a result, methods which utilize natural polymers to encapsulate drugs are more varied and polymer dependent. The following polymers are discussed in this review article: alginate, chitosan, gelatin, albumin, gliadin, pullulan, and dextran. Specialized encapsulation nanotechnologies will be discussed such as ionotropic gelation, complexation, the reverse microemulsion technique, cross-linking methods, emulsion-dependent methods, desolvation methods and self-assembly methods. For each biopolymer an overview of the structure is presented with the corresponding encapsulation techniques. Understanding the structure of the biopolymer is important as to not only understand the rational for current encapsulation techniques but to continue to develop new encapsulation techniques in pursuit of the ideal drug carrier for application in therapeutic treatments.